Suicidal behavior of cancer patients - R. V. Bisaliev (Медицинский вестник Юга России, 2024)
Objective: to analyze current data on the problem of suicidal behavior of cancer patients.Materials and methods: the analysis of 49 sources of domestic and foreign authors was carried out. The search was carried out in special medical resources, namely: RusMed, Medline, PubMed, and Web of Science. In addition, electronic libraries such as eLibrary were involved.RU, CyberLeninka and the Library of dissertations and abstracts of Russia dslib.net.Results: the theoretical analysis of scientific research has shown a significant level of prevalence of suicidal behavior in cancer patients. It should be noted that to date there are no specific scientifically based guidelines for the prevention of suicide and suicidal thoughts among cancer patients.Conclusion: preventive strategies are proposed, which show the importance of screening suicidal behavior in the general medical network in view of the high incidence of suicides to specialists.